2016
DOI: 10.3390/su8080780
|View full text |Cite
|
Sign up to set email alerts
|

Energy Performance of Hotel Buildings in Lijiang, China

Abstract: Abstract:The hotel industry in China has experienced rapid growth in the past ten years and made a considerable contribution to the global tourism economy. This paper focuses on the energy performance of hotel buildings in Lijiang, China. Hotel characteristics, daily operational data, and energy use data were collected by carrying out a survey of 24 hotels. The average annual energy use intensity (EUI) of four-, three-, two-, and one-star rated hotels was 180.8 kWh/m 2 , 113.3 kWh/m 2 , 74.2 kWh/m 2 , and 70.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Finally, the conditioned area can be estimated using digital maps or correlations such as based on the number of rooms. Examples of correlations between electricity consumption and the number of rooms for different classes of hotels are described in [14][15][16]19].…”
Section: Simplified Methods For Estimating Annual Cooling Energy Need mentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the conditioned area can be estimated using digital maps or correlations such as based on the number of rooms. Examples of correlations between electricity consumption and the number of rooms for different classes of hotels are described in [14][15][16]19].…”
Section: Simplified Methods For Estimating Annual Cooling Energy Need mentioning
confidence: 99%
“…Several studies have shown indeed that air conditioning need is responsible for most of the total electricity consumption [13][14][15][16] of tertiary buildings (i.e., hotels), and the correlation between electrical power and cooling demand has been investigated in many cases [17]. Therefore, building energy bills represent a suitable example of historical data for cooling estimation.…”
Section: Cooling Need and Electricity Consumption In Tertiary Buildingsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Chinese National Bureau of Statistics, total energy consumption in the construction industry reached 769.641 million tons of standard coal (Zhou et al, 2010). In addition, the existing hotels built in the early 21 st century lacked necessary thermal insulation measures (Ding et al, 2011;Tang et al, 2016). The practice of energy-saving renovations in existing public buildings is considered to be an essential way to reduce energy consumption and alleviate indoor climate issues (Dodoo et al, 2017;Krstic-Furundzic et al, 2019).…”
Section: Introductionmentioning
confidence: 99%